2012
DOI: 10.1200/jco.2012.30.15_suppl.2000
|View full text |Cite
|
Sign up to set email alerts
|

MGMT promoter methylation as a predictive biomarker for response to radiotherapy versus chemotherapy in malignant astrocytomas in the elderly: The NOA-08 trial.

Abstract: 2000 Background: In a few years more than half of the patients with glioblastoma will be older than 65 years of age and thus be classified as elderly. The current standard of care in elderly patients with glioblastoma (GB) or anapestic astrocytoma (AA) is resection or biopsy followed by involved-field radiotherapy (RT). The role of primary chemotherapy is poorly defined. The NOA-08 trial compared efficacy and safety of RT to temozolomide (TMZ) in patients with newly diagnosed AA or GB. Methods: Patients (N=41… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…e Analysis was limited by the small sample size for this treatment (n = 2). Median overall survival with 95% CI (horizontal lines) for each treatment cohort for the NOA-08 trial, 5 the Nordic trial, 6 the German Glioma Network study, 9 the Association des Neuro-Oncologues d'Expression Française (ANOCEF) trial, 10 European Organisation for Research and Treatment of Cancer (EORTC)-National Cancer Institute of Canada Clinical Trials Group (NCIC), 11 and the study by Rønning et al 12 Dashed line indicates mean overall survival for all patients treated; shaded area, 95% CI for mean overall survival for all patients treated. had no effect on OS in patients treated with radiotherapy in either the Nordic trial or the NOA-08 trial.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…e Analysis was limited by the small sample size for this treatment (n = 2). Median overall survival with 95% CI (horizontal lines) for each treatment cohort for the NOA-08 trial, 5 the Nordic trial, 6 the German Glioma Network study, 9 the Association des Neuro-Oncologues d'Expression Française (ANOCEF) trial, 10 European Organisation for Research and Treatment of Cancer (EORTC)-National Cancer Institute of Canada Clinical Trials Group (NCIC), 11 and the study by Rønning et al 12 Dashed line indicates mean overall survival for all patients treated; shaded area, 95% CI for mean overall survival for all patients treated. had no effect on OS in patients treated with radiotherapy in either the Nordic trial or the NOA-08 trial.…”
Section: Discussionmentioning
confidence: 99%
“…The NOA-08 trial 5 and the Nordic trial 6 were the only randomized trials comparing radiotherapy alone with temozolomide monotherapy for patients aged 65 years or older. The NOA-08 trial studied 373 patients with newly diagnosed GBM or anaplastic astrocytoma and a Karnofsky Performance Status score of 60 or greater.…”
Section: Randomized Trialsmentioning
confidence: 99%
See 1 more Smart Citation
“…5 Acceptance in the neuro-oncology community of single-modality adjuvant strategies for elderly patients with GBM generally arises from the challenges that older patients may have in completing aggressive multimodality therapies, 14,19 concerns for increased RT-related central nervous system effects in older patients, 20 and the reports of randomized trials showing no OS advantage of RT alone over temozolomide alone. 2,3 In the NOA-08 trial, 373 patients older than 65 years were randomized to dose-dense temozolomide alone vs standard RT alone (60 Gy/30 Fx) and demonstrated no significant differences in survival. 3 Similarly, the Nordic trial randomized 342 patients 60 years or older (later amended to ≥65 years) to standard dose temozolomide alone, hypofractionated RT alone (34 Gy/10 Fx), or standard fractionation RT alone (60 Gy/30 Fx), and demonstrated a prolongation in median OS with either temozolomide alone or hypofractionated RT alone over standard fractionation RT.…”
Section: Discussionmentioning
confidence: 99%
“…Although level I evidence exists to support an overall survival (OS) advantage of RT over best supportive care (BSC), 1 2 randomized trials evaluating elderly populations have demonstrated no advantage of RT alone over CT alone with temozolomide, and subgroup analyses from each of these trials suggest that CT may be the more important single-modality therapy for patients with O 6 -methylguanine-DNA methyltransferase (MGMT) promoter-methylated tumors. 2,3 Nevertheless, elderly patients who present with a favorable performance status are often suitable candidates for combined-modality therapy (CMT) with both RT and CT, which is offered as the standard of care for younger patients. [4][5][6] At present, no randomized data are available for elderly patients with GBM to clarify the effect on OS of CMT vs RT alone or CT alone.…”
mentioning
confidence: 99%